The Effect Of Information Overload On Decision Postponement Mediated By Consumer Confusion In Generation Z In Jepara - Putra, Fredyandika Bintang Pratama; Roosdhani, Mohamad Rifqy (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study aims to examine the influence of information overload on decision postponement, mediated by consumer confusion. The research adopts a quantitative approach, targeting the Generation Z population in Jepara. Data collection was conducted using completed questionnaires distributed to respondents selected through random sampling techniques and the Slovin formula. A total of 310 samples were analyzed using the PLS-SEM method with Smart PLS version 4.0. The research findings indicate that excess information does not directly influence decision postponement. However, information overload positively and significantly affects consumer confusion, and consumer confusion, in turn, positively and significantly influences decision postponement. With the presence of consumer confusion as a mediating variable, the relationship between information overload and decision postponement demonstrates a positive and significant correlation. The variable of consumer confusion in this study successfully mediates the connection between information overload and decision postponement, thereby producing positive and significant effects.